Pemberdayaan Masyarakat melalui Media Edukasi Poster Interaktif berbasis QR Code di Desa Blang Teue - zulkarnaini, Zulkarnaini; Ardilla, Arista (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2025)
Introduction: Stunting remains a major public health problem in Indonesia, including in Blang Teue Village, North Aceh, where the prevalence of children at risk of stunting reaches 28% (Public Health Center, 2023). The main contributing factors are mothers’ limited knowledge of locally sourced complementary feeding (MP-ASI) and restricted access to nutrition education media. This community service program aimed to empower the community by developing QR Code-based interactive educational posters as an accessible and user-friendly nutrition learning tool. Methods : The method employed was Community-Based Participatory Research (CBPR) with a Participatory Action Research (PAR) approach, involving 30 respondents (mothers of toddlers), health cadres, village officials, lecturers, and students. Results : The results indicated a significant improvement in mothers’ knowledge regarding local MP-ASI, where the percentage of respondents with high knowledge increased from 20% to 67% after the intervention. Utilization of QR Code media was also high, with 60% of respondents accessing it intensively, and a positive relationship was found between the intensity of media utilization and knowledge level (83% of high-intensity users achieved high knowledge). Conclusion : This program not only enhanced community knowledge and skills but also fostered the emergence of local leaders from health cadres and PKK members, as well as promoted social transformation through strengthened digital literacy and the use of local food in stunting prevention.